2021
DOI: 10.3390/app12010033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maltodextrin Replacement by Selected Native Starches and Disaccharides on Physicochemical Properties of Pumpkin Oil Capsules Prepared by Spray-Drying

Abstract: The aim of the study is to compare selected carbohydrates that differed in the glycaemic index: maltodextrin, three native starches (wheat, rice, maize), and two disaccharides (trehalose and lactose) used to encapsulation of model oil (in this case cold-pressed pumpkin oil). Encapsulation efficiency of pumpkin oil by spray drying, size of obtained capsules, oxidative stability of encapsulated oil, and retention of tocopherols, squalene, and sterols in surface and core material of capsules were determined. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Pumpkin seed oil capsules were encapsulated with different sources of starches including maltodextrin and disaccharides from wheat, rice and maize. Oxidative stability, retention of tocopherols, squalene and sterols of pumpkin seed oil was studied and results revealed that wheat starch acted as best preservative for pumpkin seed oil with enhanced antioxidant capacity and greater retention of bioactives ( Ogrodowska et al, 2021 ). Pumpkin puree was preserved during frozen storage by the application of pectin oligosaccharides, no adverse changes in structure and taste of pumpkin puree were noticed during frozen storage.…”
Section: Innovative Technologies Based Pumpkin Processing and Utiliza...mentioning
confidence: 99%
“…Pumpkin seed oil capsules were encapsulated with different sources of starches including maltodextrin and disaccharides from wheat, rice and maize. Oxidative stability, retention of tocopherols, squalene and sterols of pumpkin seed oil was studied and results revealed that wheat starch acted as best preservative for pumpkin seed oil with enhanced antioxidant capacity and greater retention of bioactives ( Ogrodowska et al, 2021 ). Pumpkin puree was preserved during frozen storage by the application of pectin oligosaccharides, no adverse changes in structure and taste of pumpkin puree were noticed during frozen storage.…”
Section: Innovative Technologies Based Pumpkin Processing and Utiliza...mentioning
confidence: 99%